N-Acetyl-L-Cysteine Reduces Cervical Carcinogenesis by Promoting Apoptosis - Wenping Guo; Wang Jing (Adis, Springer Healthcare, 2023)
Abstract Background and Objective Cervical cancer is the fourth leading cause of cancer death in women, and is one of the most common malignant tumors of the reproductive system. However, more effective treatment for cervical cancer is needed. In this study, we aim to investigate whether N-acetyl-l-cysteine (NAC) could inhibit the proliferation of human papillomavirus (HPV)-positive cells, and reduce cervical carcinogenesis. Methods The cervical cancer cell lines SiHa, HeLa, HPV-negative cell line C33A, and the immortalized human cervical keratinocyte cells S12 were used. The protein expression was determined using Western blot assay. mRNA expression was determined using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Cell proliferation was determined by Cell Counting Kit-8 assay. Cell apoptosis was evaluated using Annexin V-FITC apoptosis kits. The numbers of colonies were measured using colony-forming assay. Xenograft tumor necrosis and HPV16 E7 expression were determined using hematoxylin and eosin (H&E) staining and immunohistochemistry. Results Our results showed that NAC treatment at the concentration of 1.5 mM significantly promoted cell apoptosis and reduced cell growth by inhibiting HPV16 E7 expression. NAC inhibited HPV16-oncoprotein-induced hypoxia-inducible factor (HIF)-1α protein expression and Akt activation in vitro. Additionally, NAC suppressed tumor growth, as evidenced by the smaller tumor size in the xenograft mouse model and decreased HPV16 E7 expression in tumor tissues. Conclusion Our findings demonstrate that NAC exhibits the potential to promote HPV-positive cell apoptosis, and suppress the proliferation of HPV-positive cells by inhibiting cell inhibitor of apoptosis protein 2 and HIF-1α.